Relationship Between Diabetes Mellitus Knowledge Levels With Diabetes Mellitus Patients In Tasikmadu Health Center - Dwi Lestari Mukti Palupi; Musta'in; Windarti (LPPM Universitas Duta Bangsa Surakarta, 2019)
Data from the World Health Organization ( WHO ) states that in 2011 the number of people with diabetes mellitus ( DM ) worldwide was 346 million and projected to increase to 366 million in 2030. According to WHO and International Diabetes Federation (IDF) data estimates, explained data on the number of cases of diabetes ice in Indonesia based on the results of a 2008 survey ranks fourth highest in the world after China, India, and America, which is 8.4 million people and the estimated number exceeds 21 million in 2020. Between the various provinces In Indonesia, Central Java has a high prevalence of DM. In Indonesia, Diabetes Mellitus has ranked 4 chronic diseases based on prevalence. Diabetes mellitus is generally caused by uncontrolled consumption of food or as a side effect of the use of certain drugs. The purpose of this study looks at the relationship level of knowledge about diabetes mellitus to patient lifestyle in Tasikmadu Health center. The research used is the type of quantitative research with the design used is Quasi Experiment with one group post-test design. Data analysis in this study uses Person Correlation. The total sample study is as much as 33 patients who got Diabetes Mellitus by using the techniques of probability sampling with the kind of simple random sampling. Based on the results of the analysis of person correlation data obtained a significant value ( p-value) of 0.001 with a correlation value of person co-relation of 0.533 which means there is a relationship between the level of knowledge of diabetes mellitus on the lifestyle of people with diabetes mellitus in the work area of Tasikmadu Health Center.